Attribution Rules in the International Sports Transfer Contract - Sawsan Safi Saleh (Journal of Legal Sciences, 2024)
One of the most important social phenomena that international communities are interested in is sport, which is considered one of the parts of the economic cycle. In the past, sport was seen as abstract physical training aimed at physical and psychological development, but now it has become a source of livelihood because it is a profession practiced by man. The International Sports Transfer Contract is a positive association of the sports institution, and the acceptance of the player in a legitimate way proves its effect in its place, that is, there are two parties to this contract. Namely one party issuing a positive, and another party issuing acceptance and this contract has objective and formal conditions and specific elements like other contracts. Thus, the international sports transition contract must be surrounded by legal provisions that correspond to the financial nature of the professional sports scene. In addition, the International Sports Transfer Contract is one of the international contracts, to which the law applicable to contractual relations with a foreign element and the attribution rules stipulated by the Iraqi Civil Code No. 40 of 1951 and the Iraqi sports professionalism law for the year 2017 apply.